Sagot :
Answer:
If one of the data points has the form
(
0
,
a
)
(0,a), then a is the initial value. Using a, substitute the second point into the equation
f
(
x
)
=
a
(
b
)
x
f(x)=a(b)x, and solve for b.
If neither of the data points have the form
(
0
,
a
)
(0,a), substitute both points into two equations with the form
f
(
x
)
=
a
(
b
)
x
f(x)=a(b)x. Solve the resulting system of two equations in two unknowns to find a and b.
Using the a and b found in the steps above, write the exponential function in the form
f
(
x
)
=
a
(
b
)
x
Step-by-step explanation:
hope its help!